AYOLLARDA HAYZ SIKLINING BUZILISHLARI - Qo‘ldosheva Feruza Ibragim qizi, Qamarova Zarnigor Shamsiddinovna, Dusmurodova Maksuda G’ayratovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
this article is devoted to the gynecological diseases, which are often neglected in the coming years in teenage girls and women of childbearing age, which are taking the leading positions, that is, the types of menstrual cycle disorders. . The differences between normal menstrual cycle and pathological menstrual cycle and prophylactic measures to prevent the disease are highlighted.